Imperata economics and policy - Tomich, Thomas P.; Kussipalo, V.; Menz, K.; Byron, R.N. (1997)
Should policy makers - or anyone else - care about millions of ha of Imperata grassland? The answer depends on the balance between costs of conversion to other uses and the net benefits produced in economic growth, poverty alleviation, and protection of the environment. The first section on Imperata economics sets up the analytical framework to address this question and draws on the wider development economics literature to consider whether growth and poverty alleviation are conflicting or complementary objectives. Although evidence is limited, it suggests smallholder-based agroforestry could provide the same economic growth with greater poverty alleviation than large-scale forestry estates. There is, however, no substitute for project appraisal for specific settings. The second section on Imperata policy reviews whether policy distortions and market failures provide a sufficient rationale for direct policy intervention to promote tree planting on Imperata grasslands. Estimates of imputed values of carbon sequestration to alleviate global warming are presented for Acacia mangium and rubber agroforestry. The conclusion summarizes the policy research agenda and examines the desirability and feasibility of policy intervention to promote carbon sequestration through Imperata grassland conversion to tree-based systems.